Predictors of work inability after acute myocardial infarction in Switzerland - Fabio Barresi; Fabienne Foster-Witassek; Hans Rickli; Giovanni Pedrazzini; Marco Roffi; Milo Puhan; Holger Dressel; Dragana Radovanovic (Scientific Reports, 2024)
Abstract This study aimed to examine whether acute myocardial infarction (AMI) patients in Switzerland return to work and identify factors associated therewith. Data of 4315 working-age AMI patients enrolled in the Swiss AMIS Plus registry between 01/2006 and 09/2021 with 1-year follow-up and self-reported work status were analyzed. Patient characteristics were compared between those who did not reduce their work hours, those who reduced, and those who were no longer working 1 year after AMI. Multinomial logistic regression was used to analyze independent predictors of working ability. Of the patients, 3204 (74.3%) did not reduce their work hours, 592 (13.7%) reduced and 519 (12.0%) were no longer working 1 year after AMI. Women were more likely to reduce or stop working. Patients who did not reduce were more frequently young and male. Multinomial logistic regression showed that work reduction was associated with female sex and a Killip class > 2 at admission whereas stopping work was associated with female sex and comorbidities. A high rate of AMI patients in Switzerland (88%) return to work 1 year after AMI. Approximately 1 in 8 did not return to work and approximately 1 in 7 reduced their work hours. Important factors associated with reducing or no longer working after AMI were female sex, older age and a higher proportion of comorbidities.